Filsafat Kristiani: Antara Realitas dan Idealisme Disiplin Ilmu - Yuliantoro, Eko (Perspektif, 2006)
The relation between faith and reason has become an important issue since the rise of Christianity. When Christianity began to introduce a set of revealed truths, the authoritative power of reason was restricted by the necessity of faith in the absolute truth of Christian Revelation. As such that it substituted the role of philosophy as the way of life and the wisdom. Philosophy lost its autonomous status and hardly existed on its own. The use of philosophy was restricted to the service for defending and articulating the truth of faith as to be the handmaid for theology. However, for Etienne Gilson, The Middle Ages, which is also known the darkness era of Philosophy, provides its own dimension to characterize the unique identity of philosophy. He describes as "the spirit of Christianity penetrating the Greek tradition, working within it, drawing out of it a certain view of the world, specifically Christian," which is called "Christian Philosophy." Is Christian Philosophy a philosophy? How about the term itself? Does it seems to be self-destroying?